2022
DOI: 10.1021/acsomega.2c01160
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Oligomeric Plasticizers for Polylactide through Structural Control

Abstract: Structural variations (oligolactide segments, functionalized end groups, and different plasticizer cores) were utilized to tailor the performances of biobased plasticizers for polylactide (PLA). Six plasticizers were developed starting from 1,4-butanediol and isosorbide as cores: two monomeric (1,4-butanediol levulinate and isosorbide levulinate) and four oligomeric plasticizers with hydroxyl or levulinate ester end groups (1,4-butanediol-based oligolactide, isosorbide-based oligolactide, 1,4-butanediol-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…As shown in Figure 7A, the fracture surface of the PLA/PC4 system was almost identical and did not show visible phase separation structure. These results indicated that the plasticizer PC4 was completely miscible with the PLA matrix and formed a homogenous system after melting systeming, 8,9,18 this observation was consistent with the preceding DSC results (Figure 3). However, the surface morphologies of the PLA/PC6 and PLA/PC8 samples were different compare to that of the PLA/PC4 system.…”
Section: Isothermal Stabilities Of Pla and Its Systems Estimated By I...supporting
confidence: 91%
See 4 more Smart Citations
“…As shown in Figure 7A, the fracture surface of the PLA/PC4 system was almost identical and did not show visible phase separation structure. These results indicated that the plasticizer PC4 was completely miscible with the PLA matrix and formed a homogenous system after melting systeming, 8,9,18 this observation was consistent with the preceding DSC results (Figure 3). However, the surface morphologies of the PLA/PC6 and PLA/PC8 samples were different compare to that of the PLA/PC4 system.…”
Section: Isothermal Stabilities Of Pla and Its Systems Estimated By I...supporting
confidence: 91%
“…Therefore, to improve its processing performance, a plasticizer is added to the PLA matrix to enhance the ductility and film-forming ability of PLA. [8][9][10][11][12][13][14] Although many kinds of plasticizers 15 are available in the plastic industry, the plasticizer of PLA should be carefully selected to preserve its virtue of environmental friendliness. Hence, most PLA plasticizers belonged to aliphatic esters or low-molecular-weight aliphatic polyester without any aromatic structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations